(untitled) (Modern education and development, 2025)
This paper explores the primary morphological mechanisms involved in the creation and development of English scientific terminology, as well as the semantic evolution that accompanies terminological change over time. Affixation, compounding, blending, and neologism formation are analyzed as key word-formation processes contributing to the richness and precision of scientific vocabulary. In addition, the article examines how scientific terms undergo semantic shifts such as narrowing, broadening, and metaphorical extension due to technological and conceptual advances. The study is based on examples from modern biology, physics, computing, and medicine, with emphasis on etymological and usage-based perspectives.